Use of Healthy Family Toilets In Pangkajene Kepulauan District Village - Syafruddin, Syafruddin; Djunaedi, Djunaedi; Intang, Sitti Nur; Selvia, Selvia; Vitariani, Aisyah; Astuti, Fanni (International Journal of Health Sciences, 2024)
According to World Bank data in 2010, the existence of latrines in Indonesia is around 22%. Nationally, for urban areas it is 79% and for rural areas 49%. Most of the waste disposal is still carried out into rivers or using dug wells that do not meet the requirements, thereby polluting groundwater. Health development is essentially an effort made by all components of the Indonesian nation which aims to increase awareness, ability and desire to live healthily for everyone in order to achieve the highest level of public health (Law No. 36 of 2009 concerning Health of 2009 Article 3). One of the health developments carried out is the development of adequate sanitation for the community. This research aims to determine the factors related to the use of family latrines in Pangkep Village. Based on data from the Community Health Center, Pangkep Village is the village with the lowest percentage of households with access to healthy toilets. Research methods; using quantitative analytics with cross sectional methods complemented by qualitative analytics. The population of all 433 family heads living in Pangkep Village using stratified random sampling obtained a sample of 228 family heads. Research results; shows that there is a significant relationship between family latrine use and knowledge (p value 0.019), attitude (p value 0.014), economic status (p value 0.000), latrine ownership (p value 0.000), availability of clean water (p value 0.029 ), role of health workers (p value 0.000), as well as support from community and religious leaders (p value 0.000). The variable of latrine ownership is the most dominant in family latrine use with a prevalence risk (5.879), which means that respondents who do not have a latrine have a 5.879 times greater chance of not using a family latrine. So it can be concluded that there is still low awareness of the community in Pangkep Village using family latrines. For this reason, it is recommended that health workers continue to provide guidance and education to the community and include community participation in implementing the program.